Vitamin D in pregnancy (GRAVITD) – a randomised controlled trial identifying associations and mechanisms linking maternal Vitamin D deficiency to placental dysfunction and adverse pregnancy outcomes – study protocol - Anna Louise Vestergaard; Martin Christensen; Mette Findal Andreasen; Agnete Larsen; Pinar Bor (BMC Pregnancy and Childbirth, 2023)
Abstract Background The prevalence of vitamin D deficiency is high among pregnant women. Vitamin D deficiency in pregnancy is associated with increased risk of adverse pregnancy outcomes especially complications related to placental dysfunction and insulin resistance. The objective of this study is to investigate if a higher dose of vitamin D supplementation in pregnancy reduces the prevalence of vitamin D deficiency and prevents adverse pregnancy outcome with special emphasize on preeclampsia, foetal growth restriction and gestational diabetes. Methods GRAVITD is a double-blinded randomised trial with parallel groups where all pregnant women attending the free of charge national nuchal translucency scan programme in gestational week 10–14 at Randers Regional Hospital are invited to participate. Enrolment started in June 2020. Participants are randomised in a two armed randomization with a 1:1 allocation ratio into 1) control group – receives 10 µg of vitamin D or 2) intervention group – receives 90 µg of vitamin D. A total of 2000 pregnant women will be included. Maternal blood samples and questionnaires describing life-style habits are collected upon enrolment. For half of the participants blood samples and questionnaires will be repeated again in 3rd trimester. Blood samples will be analysed for 25-hydroxy-vitamin D using high-performance liquid chromatography coupled with tandem mass spectrometry. Upon delivery, placental tissue and umbilicalcord blood will be collected and information on maternal and fetal outcomes will be exstracted from medical records. The primary outcomes are serum levels of 25-hydroxy-vitamin D ≥ 75 nmol/L and the rate of preeclampsia, foetal growth restriction and gestational diabetes. Secondary outcome includes identification and impact on placental functions related to vitamin D. A tertiary outcome is to initiate a cohort of children born from mothers in the trial for future follow-up of the effects of vitamin D on childhood health. Discussion Provided that this trial finds beneficial effects of a higher dose of vitamin D supplementation in pregnancies, official recommendations can be adjusted accordingly. This will provide a low-cost and easily implementable adjustment of prenatal care which can improve health for both mother and child during pregnancy and beyond. Trial registration ClinicalTrial.gov: NCT04291313 . Registered February 17, 2020